SENGKETA PULAU DOKDO ANTARA JEPANG DAN KOREA SELATAN - Utami Gita Syafitri; Arif Arif; Deni Purba (Journal of USU International Law, 2013)
Abstract Dokdo Island’s dispute is a territorial dispute involving Japan and South Korea in the fight over an island located in the Sea of ​​Japan. Government of Japan and South Korea based their claim over Dokdo Island ownership on historical evidence and geographical connectivity. Dokdo Island’s dispute impede the process of negotiating maritime delimitation zone in the Sea of ​​Japan. It is necessary to immediately resolve the Dokdo Island dispute by setting limits of maritime zones Japan and South Korea, as well as provide legal certainty on the status of ownership of Dokdo Island. Claims to sovereignty over Dokdo Island is a core issue that must be resolved first. In an attempt to resolve the dispute Dokdo Island, the Government of Japan and South Korea have done several rounds of negotiations and did not find any way of settlement. Dokdo Island’s dispute resolution solutions can be made through the Joint Development Agreement, the settlement through diplomatic channels and settlement through legal channels. In order to avoid the dispute dragged on, the Government of Japan and South Korea should immediately take back the diplomatic negotiations in order to resolve Dokdo Island’s dispute. Keywords : Territorial Dispute, Dokdo Island